Toothbrushing frequency among 4-6-year-old Iranian children and associated maternal attitude and sociobehavioral factors - Raheleh Soltani; Ahmad Ali Eslami; Najmeh Akhlaghi; Gholamreza Sharifirad; Mikaeil Alipoor; Behzad Mahaki (Wolters Kluwer Medknow Publications, 2017)
Background: Toothbrushing is an important aspect of children's oral health self-care. This study aimed to explore toothbrushing frequency among 4-6-year-old Iranian children and associated maternal attitude and sociobehavioral factors. Materials and Methods: This cross-sectional study was conducted on 407 mother-child (aged 4-6 years) pairs through stratified random sampling in Tabriz, Iran. Data were collected using self-reported questionnaires including demographic characteristic, maternal attitude, and toothbrushing frequency of both mothers and children. Logistic regression was used to determine the predicators of children's toothbrushing. Statistical significance was set at P < 0.05 for all tests. Results: The mean ages were 32.6 ± 4.8 and 5.3 ± 1.1 years for mothers and children respectively. Twice-daily toothbrushing was observed at a relative frequency of 12.8% in children and 18.4% in mothers. About 43.7% of children brushed their teeth once daily. Nearly 38.7% of children started toothbrushing behavior regularly at 4 years of age, and 41% had dental visits. Multiple logistic regression analysis indicated that children's toothbrushing (once daily or more) was associated with maternal brushing frequency (odds ratio [OR] =2.0, 95% confidence interval [CI] =1.53-2.86), maternal attitude toward oral health (OR = 1.15, CI = 1.08-1.22), and children's age (OR = 1.21, 95% CI = 1.02-1.77). Conclusion: The descriptive results indicated that maternal and children toothbrushing behaviors are unfavorable. Furthermore, maternal toothbrushing behavior is a strong predicator of children's brushing behavior. Health promotional activities seem necessary for mothers to enhance oral health behavior of their children.